2020
DOI: 10.4314/ahs.v20i3.15
|View full text |Cite
|
Sign up to set email alerts
|

Unnecessary antimicrobial prescribing for upper respiratory tract infections in children in Pietermaritzburg, South Africa

Abstract: Background: Acute upper respiratory tract infections (URTIs) are contagious diseases of the upper airways, but they are self-limiting in nature. Therefore, antimicrobial-use for the majority of the URTIs is considered inappropriate. Unfortu- nately, globally, antimicrobials are still being prescribed for the treatment of URTIs, especially in children. However, there is insufficient evidence on the causes of this phenomenon in South Africa. Objective: To investigate whether the parents/guardians accompany… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…It can be categorized into acute bacterial or viral upper respiratory tract infection, among which the latter one is more common among children [ 2 ]. Acute bacterial upper respiratory tract infection is mainly diagnosed by the bacterial culture of pharyngeal swabs, which is time-consuming and not conducive enough to early diagnosis and treatment [ 3 , 4 ]. In addition, pediatric diseases usually develop rapidly, which hinders pediatricians from judging infectious diseases according to symptoms, seriously affecting the clinical relevance and prognosis of patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can be categorized into acute bacterial or viral upper respiratory tract infection, among which the latter one is more common among children [ 2 ]. Acute bacterial upper respiratory tract infection is mainly diagnosed by the bacterial culture of pharyngeal swabs, which is time-consuming and not conducive enough to early diagnosis and treatment [ 3 , 4 ]. In addition, pediatric diseases usually develop rapidly, which hinders pediatricians from judging infectious diseases according to symptoms, seriously affecting the clinical relevance and prognosis of patients [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The URTI category which included common cold, laryngitis, rhinitis, pharyngitis, rhinitis had close to 68.7% of these encounters receiving antibacterial drugs, which in most cases is inappropriate. This misuse of antibacterials as noted in numerous studies [ 18 , 19 ] is contrary to Uganda clinical guidelines recommendations of supportive treatment. A similar study in Kenya by Momanyi in Rift valley Hospital [ 20 ], we reported beta-lactam as the most frequently prescribed antibacterials class at 88.2%.…”
Section: Discussionmentioning
confidence: 84%
“…We chose to concentrate on the private sector for this study as we were aware that previous studies in South Africa had shown concerns with the prescribing habits of GPs in the private sector [ 41 , 42 , 43 , 44 ]. As mentioned, there have been concerns in other LMICs regarding the extent of inappropriate prescribing of antibiotics among physicians working in the private versus public sectors [ 22 , 79 , 80 ], and the private sector accounts for a significant minority of patients in South Africa [ 81 ].…”
Section: Methodsmentioning
confidence: 99%
“…Alongside this, Gasson et al (2018) found poor adherence to national antibiotic prescribing guidelines amongst primary care physicians in the public sector in Cape Town [ 14 ], with Matsitse et al (2017) finding similar concerns among healthcare professionals (HCPs) treating patients with sexually transmitted diseases in the public sector in South Africa [ 40 ]. Ncube et al (2017) also demonstrated high rates of antibiotic prescribing among physicians treating private patients with acute bronchitis [ 41 ], with Manderson (2020), Mathibe et al (2020) and others documenting similar concerns among physicians treating both private and public patients with acute respiratory infections [ 42 , 43 , 44 ]. However, Skosana et al (2022) in their study showed high adherence rates to South African guidelines (93.4%) when HCPs prescribed antibiotics for patients attending community health centres, with ear, nose and throat infections the most common presentation [ 37 ].…”
Section: Introductionmentioning
confidence: 99%